2014
DOI: 10.1007/s00330-014-3234-6
|View full text |Cite
|
Sign up to set email alerts
|

Image quality and cancer visibility of T2-weighted Magnetic Resonance Imaging of the prostate at 7 Tesla

Abstract: • Satisfactory to good T2-weighted image quality of the prostate is achievable at 7T. • Periprostatic lipids appear hypo-intense compared to healthy peripheral zone tissue at 7T. • Prostate cancer is visible on T2-weighted MRI at 7T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Patient studies at 7T involving prostate cancer showed until now satisfactory results for T 2 w (T 2 ‐weighted) imaging compared with 3T and the first results of 1 H and 31 P MRS at 7T were published. Imaging at 7T is technically challenging due to radiofrequency (RF) inhomogeneity, increased tissue heating, and reduced RF field penetration.…”
mentioning
confidence: 99%
“…Patient studies at 7T involving prostate cancer showed until now satisfactory results for T 2 w (T 2 ‐weighted) imaging compared with 3T and the first results of 1 H and 31 P MRS at 7T were published. Imaging at 7T is technically challenging due to radiofrequency (RF) inhomogeneity, increased tissue heating, and reduced RF field penetration.…”
mentioning
confidence: 99%
“…Some limitations of MRI are that highfieldstrength MRI systems cur rently available are not configured for intraoperative imaging and surgical guidance, and their resolution is still limited to about 200 μm per voxel in plane and 2-3 mm in the z direction. Future trends in imaging of the prostate using MRI include the introduction of magnets with a higher field strength (for example, 7 T and greater) for continued improvement in sensitivity, resolution, and image acquisition times; [91][92][93][94] however, further safety studies are w arranted before increased field strengths should be used. …”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Nevertheless, an increasing number of clinical feasibility studies at 7 T aim at regions where imaging is hampered by these severe transmit inhomogeneities, for example liver [4,5], kidneys [6], prostate [7,8], female pelvis [9], the hip joints [10,11], the heart [12], the spinal cord [13], and the breasts [14,15], or they cover extended regions such as the complete lower extremities [16].…”
Section: Introductionmentioning
confidence: 99%